Performance of a Non-Invasive System for Monitoring Blood Glucose Levels Based on Near-Infrared Spectroscopy Technology (Glucube®) - Gómez-Peralta, Fernando; Luque Romero, Luis Gabriel; Puppo-Moreno, Antonio; Riesgo, Jesús (Sensors (Basel, Switzerland), 2024)
Background: The need for frequent blood glucose (BG) monitoring and the inconveniences associated with self-monitoring of BG (SMBG) have driven the development of non-invasive approaches. Methods: This prospective study aimed to investigate the accuracy of glucose level calculation using the near-infrared spectroscopy (NIRS) technology Glucube® system. People with Type 1 diabetes, Type 2 diabetes, prediabetes, and normal glucose metabolism were included. Over one week, individuals performed glucose measurements with the Glucube® system and capillary blood fingersticks with a standard glucometer (Ascensia Contour® Next). To assess the impact of the improvement in dexterity, the accuracy variables were compared with the point-of-care (POC) glucometer Accu-Chek® Inform II in a one-week sub-study. Results: Overall, 105 subjects (mean age 53.8 ± 13.8 years, 50.5% female) participated, resulting in 1914 paired glucose measurements between 49 and 331 mg/dL. Total mean absolute relative difference (MARD) was 20.3%, MARD for values >100 mg/dL was 18.3%, and mean absolute deviation (MAD) for values <100 mg/dL was 24.9%. A total of 97.3% of measurements fell within A+B Parkes zones, and 58.8%, 76.9%, and 88.1% within +−20%, +−30%, or +−40% error, respectively. On completion, 62 participants (59%) fulfilled the one-week prospective sub-study. In this subgroup, the total MARD was reduced between day 1 and day 8 from 22.8 to 18.3% (p = 0.068). The percentages within Zone A were 51.6 vs. 61.2%, Zone B 46.8 vs. 33.9%, and Zone C 1.6 vs. 4.8%, and the sum of Parkes Zones A+B was 98.4 vs. 95.2% (p = 0.311) for day 1 and day 8, respectively. Conclusions: Glucube® is a novel non-invasive system based on NIRS technology for monitoring blood glucose levels. Its promising capabilities support further research.